An Application for Monitoring Order Set Usage in a Commercial Electronic Health Record - Cowansage, Cadran B. (American Medical Informatics Association, 2012)
Organizations that use electronic health records (EHRs) often maintain a considerable amount of clinical content in the form of order sets, documentation templates, and decision support rules. EHR vendors seldom provide analytic tools for customers to maintain such content and monitor its usage. We developed an application for tracking order sets, documentation templates and clinical alerts in a commercial electronic health record. Using the application, we compared trends in order set creation and usage at two academic medical centers over a three-year period. In January 2012, one medical center had 873 order sets available to clinicians; the other had 787. Approximately 50–75 new order sets were added each year at each medical center. We found that 46% of order sets at the first medical center and 39% at the second medical center were unused over the three-year period.